Copula lucentia sp. nov., a new box jellyfish (Cnidaria: Cubozoa: Carybdeida) from Western Mediterranean Sea - Fonfría, Eva S.; Straehler-Pohl, Ilka; Stampar, Sérgio N. [UNESP]; Collins, Allen G.; Hoverd, William Alan; Bordehore, Cesar (Springer Nature, 2024)
A new species of box jellyfish, Copula lucentia sp. nov., is described from El Campello, Spain, and compared to the holotype of Copula sivickisi that was successfully recovered after being lost for almost 60 years. So far, the only cubozoan species recorded in the Western Mediterranean was Carybdea marsupialis. The genus Copula just included the type species (Copula sivickisi) reported from different localities in the Pacific, Atlantic, and Indian Oceans. Morphologically, this new species possesses the typical characteristics of the genus Copula (four adhesive pads on the apex and a vertical keyhole-shaped rhopalial niche ostium) but it can be differentiated from the C. sivickisi holotype by the velarial canal pattern. In C. lucentia sp. nov., the velarial canal roots taper towards the velarial rim and each root bears one to two narrow triangular canals with sharp tips, resembling a bird beak. In contrast, the velarial canal roots of C. sivickisi bear two short, broad canals that increase breadth towards the velarial rim and split up into three- to six-lobed, finger-like canals with rounded tips, giving the canal pattern a paw-like appearance. Molecular analyses of mitochondrial cytochrome c oxidase subunit I (COI) and nuclear 16S ribosomal DNA genes confirm the distinction of the new species and show that there are even more Copula species than expected, but which will not be focused on here. This study highlights not only that there are species yet to be discovered in the Mediterranean Sea but that a revision of the genus Copula is necessary.
Keywords: Ecology; Morphology; New species; Taxonomy; Tripedaliidae